Reproduction system development of Ceracris kiangsu Tsai female adults and its relationship with fitness characteristics - Wang, Meizhi; Li, Hongmei; Zhang, Wei; Zhuo, Fuyan; Li, Tianjiao; Lowry, Alyssa; Zhang, Aihuan (Frontiers in Physiology, 2023)
Research on the ovarian development of insect pests helps to provide the key information for pest occurrence prediction. With the limited information and studies about the reproductive system of Ceracris kiangsu Tsai, this study used traditional methods to dissect female adults, measure female ovaries and the process of eggs’ formation, then assess the grading of the reproductive fitness from 321 adults. Next the phenotypic traits including body weight and body length were measured and used to estimate the model of ovarian developmental stages. This study found that there were four ovarian developmental stages before the oviposition, and the ovarian fundamental structure of C. kiangsu displayed red dots on the matured eggs inside the calyx at ovarian developmental stage V. The accessory glands of C. kiangsu folded the deepest at stage Ⅲ. Redundancy analysis (RDA) was used to explain the correlations during the progress of ovarian development with body weight and body length. The results indicated that significantly positive correlations were observed for body weight (p = 0.001) and body length (p = 0.009) varied with the grade of ovarian development evaluated by ovarian developmental stage, ovarian length, ovarian width, ovarian cross-sectional area. Partial least square (PLS) regression method was used to develop predictive models for estimating ovarian developmental stage. Stage-based PLS were identified as the more effective method, which was y = 1.509x1 + 0.114x2. The model provided a potential rapid way to verify the population source which are ‘native’ or ‘immigrant’ from the phenotypic traits without dissection. This may contribute to estimate the adult emergency period and analyze migratory period from the ovarian development and predict the population to take proper prevention measures.